Character Emotions in the Novel Please Look After Mom by Kyung-Sook Shin (Literary Analysis from The Perspective of Krech & Krutchfield's Psychology) - Irawati Mohamad; Mohamad Karmin Baruadi; Herman Didipu (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
The novel Please Look After Mom by Kyung-Sook Shin is a novel that describes the regret felt by each character due to the loss of their mother. Each emotion felt by the characters describes a psychological condition related to Krech & Cruthfield's psychology. This study aims to classify the forms of emotion experienced by the characters and describe the factors that cause the emotions felt by the characters in Kyung-Sook Shin's novel Please Look After Mom. This study uses a qualitative descriptive analysis approach. This study employs Krech & Crutchfield's psychological theory of emotions, utilizing a six-classification framework. Data collection techniques are carried out by reading and noting down things related to the study, then presenting the data by compiling important points. Based on the anaylisis, emotions are classified into six categories: (1) basic emotions; (2) emotions related to sensory stimulation; (3) emotions related to self-assessment; (4) emotions related to other people; (5) appreciative emotions; and (6) moods. The conclusion shows that there are 86 data points related to emotions based on this classification. The study's findings have implications for the development of literary psychology studies, particularly in understanding emotions. This research can also be utilized as literary learning material to enhance emotional awareness and deepen students’ or readers’ understanding of characters and human life. Therefore, this study is expected to broaden knowledge in the field of literary psychology and contribute to a deeper understanding of various types of emotions experienced by characters as representations of human emotional experiences.